Catalytic pyrolysis of rubbers and vulcanized rubbers using modified zeolites and mesoporous catalysts with Zn and Cu. (1st December 2019) - Yu, Jie; Liu, Sheng; Cardoso, Aderlanio; Han, Yang; Bikane, Kagiso; Sun, Lushi
Abstract: The pyrolysis-catalytic upgrading of vulcanized rubbers with metal modified zeolites were performed in order to improve oil quality and decrease sulfur content in pyrolytic oils simultaneously. Three vulcanized rubbers were synthesized by incorporating sulfur into natural rubber (NR), butadiene rubber (BR) and styrene-butadiene rubber (SBR) respectively. The catalysts of Cu/HZSM-5, Zn/HZSM-5, Cu/MCM-41 and Zn/MCM-41 were prepared using the incipient wetness impregnation method and were characterized by various means. TPD-NH3 indicated that the incorporation of Cu and Zn changed the density and strength of acid sites. Strong acidic sites were formed in Cu modified zeolites due to the occurrence of copper crystallization, which was also evidenced by XRD analysis. Due to the high dehydrogenation activity of the Lewis acidic sites introduced by the transition metals, the incorporation of Zn and Cu increased gas yields and markedly enhanced H2 formation at the expense of liquid products. GC-MS analysis showed that the catalysts can effectively reduce the polar aromatics content in pyrolytic oils. The lowest contents of polar aromatics in oils were obtained using Cu/ZSM-5, whilst the Zn/MCM-41 catalyst showed the highest selectivity towards monocyclic aromatic hydrocarbons. Zeolites can promote the decomposition of sulfur-containing components in the liquid phase into gaseous products, which was enhanced by the incorporation of metals. The catalysts modified with Zn had a better removal efficiency of sulfur-containing components. XPS analysis indicated that the Cu and Zn modified catalysts achieved desulfurization by reacting with sulfur in pyrolytic volatiles to form stable CuS or ZnS. Highlights: Introduction of Cu and Zn into zeolites promoted cracking of liquid products. Lewis acid formed by transition metals can interact with Brønsted acid. Incorporation of metals can also reduce the amount of sulfur in pyrolytic oils. Zn/ZSM-5 contributed to a higher dehydrogenation activity.